2016
DOI: 10.1126/science.aaf3552
|View full text |Cite
|
Sign up to set email alerts
|

A secreted bacterial peptidoglycan hydrolase enhances tolerance to enteric pathogens

Abstract: The intestinal microbiome modulates host susceptibility to enteric pathogens, but the specific protective factors and mechanisms of individual bacterial species are not fully characterized. We show that secreted antigen A (SagA) from Enterococcus faecium is sufficient to protect Caenorhabditis elegans against Salmonella pathogenesis by promoting pathogen tolerance. The NlpC/p60 peptidoglycan hydrolase activity of SagA is required and generated muramyl-peptide fragments that are sufficient to protect C. elegans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
151
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(163 citation statements)
references
References 49 publications
12
151
0
Order By: Relevance
“…We thus introduced sagA into a known non-pathogenic probiotic, Lactobacillus plantarum (48). Consistent with our findings with E. faecalis - sagA and E. faecium protection, sagA -expressing L. plantarum significantly prevented weight loss and improved survival upon S. Typhimurium infection compared to control L. plantarum (43). Bacterial segregation from the intestinal epithelium and MUC2 distribution were also maintained in L. plantarum - sagA -colonized mice relative to the prominent epithelial contact present in L. plantarum -vector controls (fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We thus introduced sagA into a known non-pathogenic probiotic, Lactobacillus plantarum (48). Consistent with our findings with E. faecalis - sagA and E. faecium protection, sagA -expressing L. plantarum significantly prevented weight loss and improved survival upon S. Typhimurium infection compared to control L. plantarum (43). Bacterial segregation from the intestinal epithelium and MUC2 distribution were also maintained in L. plantarum - sagA -colonized mice relative to the prominent epithelial contact present in L. plantarum -vector controls (fig.…”
Section: Resultssupporting
confidence: 91%
“…In parallel studies performed in C. elegans , we identified that a E. faecium -derived secreted NlpC/p60 peptidoglycan hydrolase, secreted antigen A (SagA), is sufficient for protection against S. Typhimurium in worms (43). Deletion of sagA has been shown to render E. faecium non-viable, and it is encoded in the genomes of all sequenced E. faecium strains (44, 45); however, sagA is absent in E. faecalis and other known commensal species (46).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conversion of primary to secondary bile salts in Clostridium scindens is associated with resistance to Clostridium difficile infection in mice and humans 107 . In Caenorhabditis elegans , the peptidoglycan hydrolase activity of the secreted antigen A from the commensal Enterococcus faecium protects against Salmonella pathogenesis 108 . In Drosophila , gut-microbiota-derived peptidoglycans, particularly from the commensal Acetobacter pomorum , prime intestinal induction of a secreted factor that is released after enteric viral infection and stimulates antiviral signaling by extracellular- signal-regulated kinases in intestinal epithelial cells 109 .…”
Section: Microbiota-driven Modulation Of the Host Immune Responsementioning
confidence: 99%
“…Examples of how microbiota induce tolerance to specific pathogens are scarce, and are largely confined to model systems. For example, a recent publication described how a peptidoglycan hydrolase produced by the commensal Enterococcus faecium can activate host cells to tolerate infection with Salmonella both in Caenorhabditis elegans and in mice (Rangan et al 2016). This tolerance to high levels of pathogenic microbes was proposed to be the result of enhanced barrier integrity, which would likely provide protection from multiple invasive microbes (Fig.…”
Section: Intestinal Bacterial Cross Talk With the Host Immune Systemmentioning
confidence: 99%